Cash Receipt Accounting Information System at Military Court I-02 Medan in 2021 - Teti Tri Astuti Jusasni; Rahmat Daim Harahap (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Every agency definitely needs an accounting information system that has been well planned and supervised, to control financial receipts. With the information system, the goals of an agency can be achieved. This study aims to analyze the effectiveness of the application of cash receipts accounting information systems in the context of financial planning and control at the military court I-02 Medan. The data used is qualitative data. The method used in this research is descriptive analysis method. The results showed that the cash receipts accounting information system for financial planning and control at the military court I-02 Medan was adequate because it was appropriate and fulfilled the basic elements of an accounting information system, namely human resources, equipment, forms/documents, records, procedures and reports, and has complied with procedures in internal control. Therefore, until now the cash receipts accounting information system at the Military Court I-02 Medan can run effectively.